Feeding Single-Walled Carbon Nanotubes or Graphene to Silkworms for Reinforced Silk Fibers - Wang, Qi; Wang, Chunya; Zhang, Mingchao; Jian, Muqiang; Zhang, Yingying (Nano letters, 2016)
Silkworm silk is gaining significant attention from both the textile industry and research society because of its outstanding mechanical properties and lustrous appearance. The possibility of creating tougher silks attracts particular research interest. Carbon nanotubes and graphene are widely studied for their use as reinforcement. In this work, we report mechanically enhanced silk directly collected by feeding Bombyx mori larval silkworms with single-walled carbon nanotubes (SWNTs) and graphene. We found that parts of the fed carbon nanomaterials were incorporated into the as-spun silk fibers, whereas the others went into the excrement of silkworms. Spectroscopy study indicated that nanocarbon additions hindered the conformation transition of silk fibroin from random coil and α-helix to β-sheet, which may contribute to increased elongation at break and toughness modules. We further investigated the pyrolysis of modified silk, and a highly developed graphitic structure with obviously enhanced electrical conductivity was obtained through the introduction of SWNTs and graphene. The successful generation of these SWNT- or graphene-embedded silks by in vivo feeding is expected to open up possibilities for the large-scale production of high-strength silk fibers.